2016
DOI: 10.1073/pnas.1513801113
|View full text |Cite
|
Sign up to set email alerts
|

Truncating PREX2 mutations activate its GEF activity and alter gene expression regulation in NRAS-mutant melanoma

Abstract: PREX2 (phosphatidylinositol-3,4,5-triphosphate-dependent Rac-exchange factor 2) is a PTEN (phosphatase and tensin homolog deleted on chromosome 10) binding protein that is significantly mutated in cutaneous melanoma and pancreatic ductal adenocarcinoma. Here, genetic and biochemical analyses were conducted to elucidate the nature and mechanistic basis of PREX2 mutation in melanoma development. By generating an inducible transgenic mouse model we showed an oncogenic role for a truncating PREX2 mutation (PREX2E8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 51 publications
5
63
0
Order By: Relevance
“…Finally, the PREX1-related RhoGEF PREX2 is activated by missense mutations in 25% of metastatic melanomas, especially by truncating mutations mutations (11,12), and mutational activation of the PREX1/2 target RAC1 has been observed in ~11% of melanomas (15,16). The rarity of PREX1 truncating mutations and lack of apparent hotspots among the few missense mutations argue that this is not a significant mechanism of PREX1 activation in melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the PREX1-related RhoGEF PREX2 is activated by missense mutations in 25% of metastatic melanomas, especially by truncating mutations mutations (11,12), and mutational activation of the PREX1/2 target RAC1 has been observed in ~11% of melanomas (15,16). The rarity of PREX1 truncating mutations and lack of apparent hotspots among the few missense mutations argue that this is not a significant mechanism of PREX1 activation in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, missense mutations in PREX2 have been identified in 25% of malignant melanomas (11). Although no clear mutational hotspots have been seen in melanomas, experimental studies support a gain-of-function consequence of these mutations (11,12). PREX2 missense mutations have also been found in 38% of cutaneous squamous cell carcinomas (13) and 17% of stomach adenocarcinomas (14).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas P-Rex1 mutations are infrequent, a high incidence of P-Rex2 point mutations has been described in melanoma (14%, third in prevalence after BRaf and NRas) (38). Although the biological consequences of the multiple P-Rex2 mutations, observed in melanoma and pancreatic cancer, have yet to be fully determined, a recent study has demonstrated enhanced Rac1-GEF activity and a pro-tumorigenic function of a truncated P-Rex2 mutant (39). …”
Section: Emerging Paradigms In Rho Gtpase Hyperactivation In Cancermentioning
confidence: 99%
“…PREX2 is also overexpressed in numerous cancer types and is frequently mutated in cancer, with especially high mutation rates in melanoma (25)(26)(27). PREX2 mutations found in cancer activate its GEF activity and promote tumorigenesis in a melanocyte xenograft mouse model (27,28). Furthermore, certain mutations can also evade PTEN-mediated inhibition of PREX2-driven breast cancer cell invasion (29).…”
mentioning
confidence: 99%